FUNGSI DINAS KESEHATAN KOTA PEKANBARU DALAM MENGURANGI ANGKA KEMATIAN IBU DAN ANAK DI KOTA PEKANBARU PERIODE 2018-2019 - Adib Murtadho Aslam; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Improving maternal health has become the main priority of the government, various efforts have been made by the government to improve maternal health. The progress of a country, in essence, is inseparable from the quality of maternal and child health, because from a good mother's health, the next generation of responsible nations will be born. However, until now it is still marked by the vulnerable health status of mothers and children, especially in the most vulnerable groups, namely pregnant, maternity and postpartum women, as well as newborns, which causes the still high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Pekanbaru City is the capital of Riau Province with the highest MMR and IMR in Riau Province, while from 2015 - 2018 cases continued to increase and fell in 2019, although not significantly. Based on these problems, the formulation of the research problem is: "What is the function of the Pekanbaru City Health Service in Reducing Maternal and Child Mortality Rates in Pekanbaru City 2018 - 2019? This research is a type of descriptive research using a qualitative approach. Data collection techniques in this study used interviews, observation and documentation techniques, the data analysis used was qualitative analysis. The findings that can be concluded from the function of the Pekanbaru City Health Office in Reducing Maternal and Child Mortality Rates in Pekanbaru City in 2018 – 2019 are: 1) The government, in this case the Health Office, implements rules related to preventing maternal and child mortality, especially having a Strategic Plan and Rena; 2) Development, provision of facilities and infrastructure, but specifically at the puskesmas Alkes are classified as incomplete and referred to hospitals, moreover the budget for these provision is relatively minimal; 3) Service function, the Health Office provides health services such as counseling, direct monitoring, health infrastructure, etc. However, the SPM target for the Health Office was not achieved; 4) The empowerment function, by empowering the potential of medical personnel by conducting counseling, going to the field is considered less than optimal because the medical staff are not friendly so that the community chooses to support them, as well as the lack of public knowledge about maternal and child health. Keywords: Functions of Government, MMR, IMR.